Attacking currency trends : how to anticipate and trade big moves in the forex market - Michalowski, Greg. (Hoboken, N.J. : John Wiley & Sons, 2011)
'Attack the Currency Trend will provide traders with a step-by-step guide for anticipating, entering, and staying with trends in the foreign exchange market. Top forex expert Greg Michalowski begins the book by explaining the attributes of successful traders, and how traders should set themselves up for success by drafting an explicit mission statement and game plan. From there, he provides tools and techniques for traders to read the markets and identify when a market is in a trend. Michalowski shows traders how to enter an emerging trend, how to manage the position, and how to exit the position most effectively. He advocates using fairly simple technical tools: moving averages, trendlines, and Fibonacci levels. The important thing is to use these tools to get a feel for trends, and then to move aggressively into a position once the trend is identified and stick with the trend through its duration.'--
Includes index.
Keywords: Foreign exchange market -- Handbooks, manuals, etc; Investments -- Handbooks, manuals, etc; Foreign exchange -- Handbooks, manuals, etc